The General Impossibility of Normative Accounting Standards. - Demski, Joel S. (The Accounting Review, 1973)
We have interpreted accounting theory as providing a complete and transitive ranking of accounting alternatives at the individual level. It was then proven that no set of standards (applied to the accounting alternatives per se) exists that will always rank accounting alternatives in relation to consistent individual preferences and beliefs. The major import of the result is to raise a number of questions. We know that standards do not always work. When, then, do they work? Under what types of conditions will various types of standards work; when they fail, how badly do they fail? We know that criteria systems, as in information theory, ASOBAT, or cost-allocation guides cannot be relied upon to provide the desired result in every situation. This does not, however, necessarily imply that they never provide the desired result. Hence, a major question in accounting theory must be conditions under which standards do work.